Tindakan Preventif Orang Tua dalam Menyikapi Kenakalan Mr.X di Kecamatan Tallo, Kota Makassar - Nur Alifia; Sam’un Mukramin (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Juvenile delinquent behavior, such as that experienced by Mr. X, has a serious impact on the development of the individual, the family, and society as a whole. Therefore, it is important for parents to play an active and effective role in addressing the delinquent behavior exhibited by their child. The research method used is a qualitative research method with a case study approach. Data is obtained through in-depth interviews with parents, as well as direct observation of the interaction between parents and children. The data collected will be analyzed thematically to identify the strategies used by parents in addressing juvenile delinquency. The results of this study conclude that parents' preventive actions in addressing Mr. X's juvenile delinquency in Kaluku Bodoa, Tallo sub-district, Makassar city are very important. Through a directed approach, effective communication, proper supervision, and consistent support, parents can play an active role in helping adolescents overcome delinquency and guide them towards more positive behavior.